50th Anniversary of Acta stomatologica Croatica - Hrvoje Brkić (University of Zagreb. School of Dental Medicine, 2016)
Acta stomatologica Croatisa (ASCRO) is scientific-professional magazine whose first issue was published back in 1966. Ever since the magazine publishers were the School of Dental Medicine of the University of Zagreb and the Croatian Dental Association of the Croatian Medical Association. Over the past fifty years two hundred regular editions were pubslihed along with three additions. The magazine has been internationally indexed and it was granted the DOI number. In this way by means of CrossCheck possible plagiarisms are being checked which aims at obtaining originality of the published results. Another peculiarity of ASCRO is bilingualism throughout the whole edition, international recognizability, open source and tradition based on sound foundations.